Genetic characterisation of a novel reptarenavirus detected in a dead pet red-tailed boa (Boa constrictor) - Ihász, Katalin; Marton, Szilvia; Fehér, Enikő; Bányai, Krisztián; Farkas, Szilvia L (Acta veterinaria Hungarica (Budapest. 1983), 2022)
Boid inclusion body disease (BIBD) is a severe and transmissible disease of snakes worldwide. Reptarenaviruses have been identified as the aetiological agents of BIBD. We determined the almost complete genome sequence of an arenavirus detected in a female red-tailed boa that had succumbed in a private collection in Hungary. We used a combination of next generation sequencing and Sanger sequencing methods. Based on the analysis of the obtained sequence data, the virus, tentatively named Coldvalley virus, seemed to belong to the Reptarenavirus genus of the Arenaviridae family. This classification was confirmed by the genome structure (bisegmented single-stranded RNA) characteristic of the genera Mammarenavirus and Reptarenavirus. The pairwise comparison of the nucleotide and amino acid sequences, as well as the topology of the maximum likelihood phylogenetic trees, suggested that the newly-characterised Coldvalley virus can be classified into the species Rotterdam reptarenavirus.